SARS-CoV-2 Infection in Cancer Patients: A Picture of an Italian Onco-Covid Unit - Reale, Maria Lucia; Bironzo, Paolo; Bertaglia, Valentina; Palesandro, Erica; Leone, Gianmarco; Tabbò, Fabrizio; Bungaro, Maristella; Audisio, Marco; Mariniello, Annapaola; Rapetti, Simonetta G.; Di Stefano, Rosario F.; Artusio, Elisa; et al. (Frontiers in Oncology, 2020)
Background: The world, and Italy on the front lines, has experienced a major medical emergency due to the novel coronavirus outbreak. Cancer patients are one of the potentially most vulnerable cohorts of people, but data about their management are still few. Patients and methods: In this monocentric retrospective study we included all SARS-CoV-2 oncological patients accepted, between March 27th to April 19th 2020, at the Onco-COVID Unit at San Luigi Gonzaga Hospital, one of the few Italian oncological-COVID wards. Data were obtained from medical records. Results 18 cancer patients with COVID-19 were included. The mean (±SD) age of patients was 67±14 years, 89% were men. Seven (39%) developed infection in communities and 11 (61%) during hospitalization. Lung cancer was the most frequent type of cancer (10, 56%). Seven patients (39%) were symptomatic for COVID-19 at the time of diagnosis and symptoms began 2 (±2) days before. The most common were shortness of breath and diarrhea. Fever was present in 5 patients (28%). Among the 11 asymptomatic patients, 8 (73%) became symptomatic during the hospitalization (mean time of symptoms onset 4 days + 4). Six patients (33%) were on active anti-tumor treatment: 2 (33%) received anti-tumor therapy within two weeks before the infection diagnosis and 2 (33%) continued oncological treatment after SARS-CoV-2 positivity. Eight (44%) patients died within a mean of 12 days (+ 8) from the infection diagnosis. Conclusions: Our series confirms the high mortality among cancer patients with COVID-19. The presence of asymptomatic cases evidences that typical symptoms and fever are not the only parameters to suspect the infection. The Onco-Covid unit suggests the importance of a tailored and holistic approach, even in this difficult situation.